O FENÔMENO PAUSA COMO PISTA PARA AVALIAÇÃO DE FLUÊNCIA EM PORTUGUÊS DO BRASIL COMO SEGUNDA LÍNGUA - Soares, Lia Abrantes Antunes (BELT - Brazilian English Language Teaching Journal, 2015)
Fluently communicating in a target language, especially in a situation of oral assessment, is a common goal among learners. However, scholars and teachers in the area of second language agree that it is difficult to define fluency, so how can it be evaluated? Studies show that the phenomenon of pausing is an important factor in the perception of non-native speech. In this article, we assume that not every pause should be considered a characteristic of non-fluent speech. One of the factors that guide natives’ perception about whether foreign language learners speak fluently or not is the pause for modification. This article describes how, when and why such modifications are common in the speech of learners. The physical and cognitive description of pauses undertaken through oral narratives of Brazilian Portuguese learners has yielded significant results for distinguishing levels of fluency, giving us clues for a description of fluency in the grid of oral assessment.